Machining and Tool Wear Mechanisms during Machining Titanium Alloys - Islam, Mohammad Nazrul; Pramanik, Alokesh; Basak, A.; Littlefair, G. (Trans Tech Publications Inc, 2013)
This paper investigates the machining mechanism of titanium alloys and analyses those understandings systematically to give a solid understanding with latest developments on machining of titanium alloys. The chip formation mechanism and wear of different cutting tools have been analyzed thoroughly based on the available literature. It is found that the deformation mechanism during machining of titanium alloys is complex and it takes place through several processes. Abrasion, attrition, diffusion–dissolution, thermal crack and plastic deformation are main tool wear mechanisms.